B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma: Report of a case in the oral cavity - Jumana M Jaradat; Anitha Potluri; Elizabeth A Bilodeau (Wolters Kluwer Medknow Publications, 2013)
B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma (DLBCL/BL) is a new category of B-cell lymphoma according to the 4 th edition of the World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissues (2008). The following report presents a case of this rare, newly described entity on the palate of a 59 year-old male.